Fabrication of phosphorus-mediated MoS2 nanosheets on carbon cloth for enhanced hydrogen evolution reaction. (12th May 2022) - Tian, Jingyang; Yang, Chundi; Hao, Ruihua; Li, Funan; Liu, Zhirui; Chen, Wei; Lv, Yuancai; Lin, Chong
Abstract: Molybdenum sulfide (MoS2 ) as a graphene-like sheet material has attracted wide attention owing to the potential for hydrogen evolution reaction (HER). However, the large-scale application of MoS2 is still difficult due to the inherent poor conductivity and insufficient active edge sites. Herein, we develop a simple method to grow P-doped MoS2 nanosheets on carbon cloth for high efficiency HER. The 2D carbon cloth can prevent the stacking of MoS2 nanosheets and improve the conductivity with the doping of P atoms. As a result, the P–MoS2 /CC-300 shows the excellent electrocatalytic activity with an overpotential of 81 mV at 10 mA cm −2 and the lower Tafel slope of 98 mV/dec. Furthermore, it also shows the good electrocatalytic durability for 15 h. This work provides an opportunity for the design of excellent and robust MoS2 -based catalyst via structural engineering and doping method. Graphical abstract: The P-doped MoS2 nanosheets on carbon cloth was developed for efficient hydrogen evolution reaction. Image 1 Highlights: The P-doped MoS2 nanosheets grown on carbon cloth was synthesized. The P–MoS2 /CC-300 performs the excellent electrocatalytic activity. The P–MoS2 /CC-300 can also display the outstanding electrocatalytic durability for 15 h.